Research on the characteristics and innovation paths of news dissemination on social media platforms - Sun, Jingyue (Transactions on Social Science, Education and Humanities Research, 2024)
In the era of new media, social media platforms should pay attention to the innovation of news content, improve interaction, achieve accurate push and cross-platform cooperation and other innovation paths, so as to meet the diversified needs of users and promote the development of news communication. This paper aims to explore the characteristics of news communication on social media platforms and analyze its innovation path in the new media era. Through the case analysis of multiple social media platforms, combined with news communication theories, this paper deeply studies the characteristics of social media news communication, such as speed, interactivity and personalization, and puts forward corresponding innovative strategies, in order to provide useful references for news communication practice.